634 Production and testing of a novel bispecific nanobody construct targeting NK cells and EGFR expressing malignancies. (9th November 2020) - Toffoli, Elisa; Sheikhi, Abdolkarim; Lameris, Roeland; King, Lisa; Tuynman, Jurriaan; Spanholtz, Jan; Verheul, Henk; Gruijl, Tanja de; Vliet, Hans Van der
Abstract : Background: The ability to kill tumor cells with an acceptable toxicity profile, makes Natural Killer (NK) cells promising assets for cancer therapy. However, strategies to enhance the preferential accumulation and activation of NK cells in the tumor microenvironment would likely increase the efficacy of NK cell-based therapies. Methods: In this study, we show a novel bispecific nanobody-based construct (biVHH) targeting both CD16A (low-affinity Fc receptor: FcRγIIIA) on NK cells and EGFR on tumors of epithelial origins. Results: Higher levels of NK cell activity and subsequent tumor cell lysis were found in vitro in the presence of the biVHH and were dependent on the expression of both CD16A and EGFR while they were independent of the KRAS mutational status of the tumor. Increased NK cell activity was found in NK cells derived from colorectal cancer (CRC) patients when co-cultured with the biVHH and EGFR expressing tumor cells. Finally, higher levels of cytotoxicity were found against patient-derived metastatic CRC cells in the presence of the biVHH and autologous peripheral blood mononuclear cells or allogeneic NK cells. Conclusions: Based on our results, the bispecific CD16A and EGFR targeting VHH construct could be a useful tool in combination with various NK cell-based therapies.